Report of the Selected Buildings Projects Team on Multistoreyed Buildings - Committee on Plan Projects Planning Commission (Planning Commission, Government of India, 1958)
The Report on Multistoreyed Buildings evaluates the planning, design, execution, and administrative practices associated with major multi-storeyed public building projects in India. It highlights inefficiencies in space utilization, wide regional cost variations, and recurring delays caused by inadequate planning, late approvals, material shortages, and frequent design changes during execution. Emphasizing the need for standardized norms, the report recommends optimal carpet area ratios, improved site management, rigorous quality control, and the adoption of modern construction techniques such as prefabrication and welding. It also advocates selective tendering, detailed pre-construction programming, and continuous monitoring by dedicated authorities. Together with comparative construction case studies, the report underscores the importance of integrated planning and administrative reform to enhance cost efficiency, structural quality, and functional performance of multistoreyed buildings in India’s urban development efforts.
Committee on Plan Projects New Delhi, December 1958
Keywords: Multistoreyed Building Planning; Selected Buildings Projects Team; Carpet Area Efficiency Norms; Urban Space Utilization; Construction Cost Variations; Design Orientation Standards; Administrative Approval Delays; Material Supply Constraints; Quality Control in Construction; Prefabrication and Welding Techniques; Selective Tendering Policy; Public Building Project Management